Synthesis Strategy of Cinnamaldehyde Derivate Compound from Cinnamon Bark Oil (Cinnamomum burmanii) to 2-hydroxycinnamaldehyde - Vina Octavia Azzahra; Warsito Warsito; Elvina Dhiaul Iftitah; Desytrifa Rosenny Ompusunggu; Dwi Nanda Cakra Wiguna; Fadhil Akbar Sugiarto (Jurnal Kimia Valensi, 2022)
Cinnamaldehyde is the major secondary metabolite of Cinnamon (Cinnamomum burmanii) that has various benefits in medical fields. One of the cinnamaldehyde derivatives, 2-Hydroxycinnamaldehyde (HC), has been shown to have good anticancer activity. In contrast to its activity, the synthesis method of HC from pure cinnamaldehyde has not been studied before. This research studies the synthesis of HC with a semisynthetic approach from the natural ingredient cinnamaldehyde. This study was initiated by purifying cinnamaldehyde from cinnamon bark oil with the salting method using a saturated sodium bisulfite solution. Cinnamaldehyde is converted into HC through the synthesis design in three-reaction steps, including nitration using nitric acid-acetic acid anhydride at 0-5 °C, reduction in mild condition by reflux using NH4Cl-Fe in methanol-water solution, and diazotation-hydrolysis using NaNO2-HCl at 5 °C. Optimization of the synthesis was evaluated to get the best method according to yield and characterized using TLC, UV-Vis, FTIR, and GC-MS/LC-MS. The isolated CD has a purity of up to 100% with a yield of about 36%. The 2-nitrocinnamaldehyde (NC) product from nitration was analyzed with ethanol and n-hexane (1:1) Rf = 0.84 and showed high purity with a 26% yield. The reduction product 2-aminocinnamaldehyde (Rf = 0.48) and 2-hydroxycinamaldehyde (Rf = 0.19) as a product from diazotation-hydrolysis obtained in moderate yield.